المقاربة الإبستيمولوجية لموضوع علم الاستغراب: An Epistemological Approach to The Subject of Occidentalism - bin Fadil Bouchair, Abdulaziz; Alshighaybi, Mohammed Salem (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This study examines the epistemological foundations and methodological conditions for establishing Occidentalism as a systematic scientific discipline, with the West as its primary subject of research. Focusing on contemporary Islamic thought, it addresses how the Islamic mind can critically engage with Orientalist discourse and construct knowledge about the West. Using analytical, inductive, and critical methods, the study identifies the need to move Occidentalism from mere accumulation of knowledge to a structured science guided by a clear epistemological vision. Key recommendations include distinguishing between the study of the West and the science of Occidentalism, defining its subject and scope, overcoming epistemological obstacles, and integrating insights from both Western and Islamic scholarship to organize and classify its topics systematically.